(untitled) (Revista horizonte, 2022)
The main objective of this researching was to determine the effect of visual mental practice (VMP) on total time (TT) when a combination of kicks it’s been executed. A group of 15 members from a College Taekwondo team participated voluntarily and they were distributed by grade/belt and gender, on groups of physical practice (PP) or VMP. The researching was developed in two sessions. In the first session the skill was taught to both groups, after two attempts the pre-test was applied, the skill ?s TT was evaluated by the SmartspeedPro ?s photocells and the technical mistakes were penalized by adding a standard deviation to the TT. The practice for each group lasted twelve minutes, the PP group made coordination exercises and the VMP group made the sequence of executed kicks. Then the acquisition test was applied and one week later, the retention test. When a mixed 2-way ANOVA with repeated measures was applied in the last factor [group (2) x measurement (3)] it showed that there was no significant differences, which allows us to conclude that, under the conditions that we performed the study, neither the VMP nor the PP represented an effect over the TT when the taekwondo practitioners executed the combined kicks. We recommend the increase of the session ?s time.